FAKTOR INTERNAL DAN PENGARUH NYA TERHADAP RISK PERCEPTION DAN EXPECTED RETURN PERCEPTION - AKHMAD ANDRIYANTO W; Anik Malikah; Afifudin Afifudin (Universitas Islam Malang, 2018)
ABSTRACTThis research was conducted in order to examineinternal factors (overconfidence, experience, emotion, mental accountingand position of wealth) and their effects on risk perception and expectedreturn perception. The sampling technique used was purposive samplingwith criteria including (1) active investors investing in IndoPremierSecurities Branch Malang. (2) Investors who actively invest in the researchyear (2018). The population in this study were investors in IndoPremiersecurities Malang Branch, and the sample used was 135 respondents. Theanalysis technique used in this study is multiple linear regression. Theresults showed that simultaneously there was a significant positive effectbetween internal factors with risk perception and expected returnperception. And partially between internal factors with risk perception onlyoverconfidence, and experience variables that significantly influence therisk perception. Conversely, between internal factors and expected returnperception only the overconfidence, experience, and mental accountingvariables significantly influence the expected return perception. The R2 testof this study was 0.211 or 21% in the dependent variable risk perceptionand for the dependent variable expected return perception was 0.46 or46.2%.Key Words: Overconfidence, experience, emotion, mental accounting,position of wealth, risk perception and expected returnperception